PROSPECTS FOR THE DEVELOPMENT OF BRAIN CYTOLOGICAL EXAMINATION IN PNEUMOCONIOSIS IN MINERS - Бондарев, Олег Иванович; Филимонов, Сергей Николаевич (Medicine in Kuzbass, 2023)
Coal industry workers are characterized by a high level of occupational diseases, including pneumoconiosis. The current level of diagnosis is based on clinical research methods, which often do not determine early changes in the lungs. Knowledge in the field of studying pneumoconiosis contains many contradictions in the diagnostic assessment of lung damage, in particular changes in the respiratory system at the initial stage of the disease without clinical manifestations. The study is devoted to early cytological examination of miners working in underground conditions. The task is to identify early morphological manifestations of dust pathology in miners, based on cytological research.The purpose of the study – morphological study of early cytological changes in bronchial epithelium and broncho-alveolar cell associations in miners with bronchopulmonary dust pathology of professional genesis.Material and methods of research. Cytological examination of bronchi obtained during 50 forensic medical examinations of miners who died simultaneously while working in the mine during a man-made disaster, 50 broncho-alveolar and bronchial flushes in patients with suspected bronchopulmonary pathology was carried out. Prints from the surface of the bronchial mucosa stained with Papenheim and hematoxylin-eosin were studied.Results. During cytological examination of bronchial flushes and broncho-alveolar lavage (BAL), in the prints of coal industry workers, compared with the norm, an increase in the quantitative indicators of cellular elements was reliably observed, the number of macrophages and actively phagocytic alveolar macrophages (AM) sharply increases. Dysmetabolic signs of morphometric indicators of all cellular generations of the exfoliated cells of the alveolar and bronchial epithelium also increase, and the number of metaplastic epithelial cells appear and increase.Conclusions.1.      The data obtained during cytological examination can be used for an early screening test of occupational bronchopulmonary pathology during occupational examinations of miners.2.      An early cytological sign of the developing pneumoconiotic process in the preclinical stage is the detection in bronchial smears-prints, including with BS and BAL, of a sharp increase in the number, size and large «loading» with dust particles of the cytoplasm of AM (coniophages), the presence of various degrees of dystrophy and squamous epithelial metaplasia of the bronchial epithelium.3.      Cytological examination data will more effectively allow the early prevention of pneumoconiosis.4.      These cytological studies will expand the differential diagnostic capabilities of the method for determining dust pathology from other pathological changes in the bronchopulmonary system and, first of all, oncopathological processes.
Keywords: miners; dust pathology of the lungs; cytology; cytohistochemical study